A 10-year review of child injury hospitalisations, health outcomes and treatment costs in Australia. Issue 5 (27th July 2017) - Mitchell, Rebecca J; Curtis, Kate; Foster, Kim
Abstract : Background: Childhood injury is a leading cause of hospitalisation, yet there has been no comprehensive examination of child injury and survival over time in Australia. To examine the characteristics, temporal trend and survival for children who were hospitalised as a result of injury in Australia. Method: A retrospective examination of linked hospitalisation and mortality data for injured children aged 16 years or less during 1 July 2001 to 30 June 2012. Negative binomial regression examined change in injury hospitalisation trends. Cox proportional hazard regression examined the association of risk factors on 30-day survival. Results: There were 6 86 409 injury hospitalisations, with an age-standardised rate of 1489 per 1 00 000 population (95% CI 1485.3 to 1492.4) in Australia. Child injury hospitalisation rates did not change over the 10-year period. For every severely injured child, there are at least 13 children hospitalised with minor or moderate injuries. The total cost of child injury hospitalisations was $A2.1 billion (annually $A212 million). Falls (38.4%) were the most common injury mechanism. Factors associated with a higher risk of 30-day mortality were: child was aged ≤10 years, higher injury severity, head injury, injured in a transport incident or following drowning and submersion or other threats to breathing, during self-harm and usual residence was regional/remote Australia. Conclusions: Childhood injury hospitalisation rates have not reduced in 10 years. Children's patterns of injury change with age, and priorities for injury prevention alter according to developmental stages. The development of a national multisectorial childhood injury monitoring and prevention strategy in Australia is long overdue.